Transporte reativo de contaminantes nitrogenados em zonas vadosa e saturada na bacia do Riacho dos Macacos em Juazeiro do Norte – Ceará - Almeida, João Roberto Façanha de (2015)
The sedimentary aquifers present in the south of Ceará hold important natural water resources for the population of this region, because of their good quality and great availability. However, they constitute fragile resources being susceptible to degradation processes by human action. The objective of this research is to deepen the knowledge of the hydrogeochemistry of the medium aquifer in Juazeiro do Norte and understand the dynamics of transport of nitrogenous contaminants in the Riacho dos Macacos watershed area. For this purpose, Stiff diagrams and statistical analysis of hierarchical clustering were applied in hydrochemical monitoring data of 26 wells, totaling 158 samples, collected between the years 2010 and 2014, and data from pumping tests were used in groundwater flow simulations for modeling the transport of contaminants in the vadose and saturated zones. Stiff diagrams showed the classification of waters according to the presence of the dominant ions, where water quality showed changes for dry and wet periods: cluster analysis was able to differentiate groups with different water quality. A groundwater flow model was generated using Visual MODFLOW Classic software, which, properly calibrated and validated, identified the hydraulic head in the aquifer in 2015 and map the thickness of the vadose zone where biological transformation processes of nitrogen compounds by oxidation reactions happen. PHREEQC interactive software simulations showed that the vadose zone allows the input of significant concentrations of nitrate to groundwater, and sewage from septic tanks is also an important source of groundwater contamination. Aquifer exploitation scenarios were simulated and showed that an increase in nitrate release into the aquifer can degrade the water quality of most wells reaching levels which impede their use. On the other hand, a gradual reduction of the contaminant load can ensure the recovery of water quality throughout the wellfield in about ten years; while a sudden cut of sewage release into the drainage channel and the Riacho dos Macacos creek promotes a reduction in nitrate concentration to acceptable levels within about two years throughout the aquifer